Pendampingan Penyusunan Konten Promosi TikTok Berbasis Storytelling dan Call to Action bagi Pengelola Promosi Hotel Siliwangi Semarang - Isnani Baid Maulida Putri; Naina Zhara Ananda; Diah Sukmawati; Yogi Swaraswati; Sugiharto Sugiharto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The digital marketing transformation in the hospitality industry requires promotion managers to create social media content that is not only informative but also persuasive and aligned with platform characteristics. Hotel Siliwangi Semarang has utilized a TikTok account for promotion; however, preliminary observations from January to March 2026 revealed that uploaded content was dominated by showcasing facilities averaging 433 views and 5 likes per video and lacked strength in storytelling and Call to Action (CTA) elements. This community service activity aimed to enhance the hotel promotion team's ability to create TikTok promotional content incorporating storytelling and CTAs. The activity took place from April 6–9, 2026, employing a participatory training and mentoring approach with 12 participants. The stages included preliminary observation, training, content creation practice, three days of mentoring, and evaluation. Evaluation was conducted using an observation sheet covering six aspects: storytelling, captions, information clarity, visual CTAs, and the integration of storytelling and CTAs. Each aspect was rated on a scale of 1 to 5, where 1 indicated the aspect had not been implemented and 5 indicated excellent implementation. Results showed that the program successfully improved participants' capabilities. The total score rose from 15 (50%) before the activity to 24 (80%) afterward, with the most significant improvements observed in storytelling, CTAs, and the integration of storytelling and CTAs. TikTok account performance also improved, evidenced by an increase in uploads from 10 to 15 videos, average views rising from 433 to 1,626 per video, and average likes increasing from 5 to 21 per video though these results should be interpreted with caution due to the influence of external platform factors. In conclusion, the training and mentoring on creating storytelling- and CTA-based TikTok promotional content successfully enhanced participants' ability to produce digital promotional content that is more structured, persuasive, and aligned with TikTok's characteristics.